Preparing Latino Students for Life After High School: The Important Role of School Counselors and School Psychologists - Desiree Vega; Erik Hines; Renae Mayes; Paul Harris (National Youth Advocacy and Resilience Journal, 2016)
Latinos represent a significant percentage of the U.S. population; yet, they continue to experience substantial educational challenges in society. The purpose of this paper is to explore the barriers Latino students face in pursuit of educational opportunity and the important role school counselors and school psychologists can play in preparing them for life after high school, whether it be participation in the workforce or attendance at a postsecondary institution. Policy recommendations are provided for educators and policymakers at the secondary and postsecondary levels. Moreover, practice recommendations are offered for school counselors and school psychologists at the secondary level.